2020
DOI: 10.3390/diagnostics10010023
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Contrast-Enhanced Harmonic Endoscopic Ultrasonography for Early Diagnosis of Small Pancreatic Cancer

Abstract: This study aimed to assess whether contrast-enhanced harmonic endoscopic ultrasonography (CH-EUS), compared to multidetector-row computed tomography (MDCT) and magnetic resonance imaging (MRI), is useful for early diagnosis of small pancreatic cancer (PC). Between March 2010 and June 2018, all three imaging modalities and surgery were performed for patients with a pancreatic solid lesion measuring ≤20 mm; diagnostic ability was compared among modalities. Fifty-one of 60 patients were diagnosed with PC (PC size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Contrast-enhanced EUS (CE-EUS) increases the detectability of vessels and can overcome some of these limitations. Indeed, many studies demonstrate the utility of CE-EUS for diagnosis of pancreatobiliary lesions [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]; thus, the technique is used widely in the clinic. However, there are some problems.…”
Section: Introductionmentioning
confidence: 99%
“…Contrast-enhanced EUS (CE-EUS) increases the detectability of vessels and can overcome some of these limitations. Indeed, many studies demonstrate the utility of CE-EUS for diagnosis of pancreatobiliary lesions [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]; thus, the technique is used widely in the clinic. However, there are some problems.…”
Section: Introductionmentioning
confidence: 99%
“…[ 21 22 ] Another Japanese study confirmed these data and showed superiority of CE-EUS in diagnosing early pancreatic cancer (≤20 mm) compared to MDCT and magnetic resonance imaging (MRI). [ 22 ] The clinical accuracy of CE-EUS for the diagnosis of PDAC versus non-PDAC lesions in pancreatic solid lesions <15 mm has been confirmed in a recent multicenter trial including 219 patients, indicating an overall 89% accuracy of CE-EUS. [ 20 ] Recently, time–intensity curve analysis has also been used with a high diagnostic accuracy of 91% to characterize focal pancreatic lesions.…”
Section: Introduction and Review Of The Literaturementioning
confidence: 91%
“…[ 20 ] In a Japanese study, the sensitivity of CE-EUS was 91.2%, while the corresponding sensitivity of contrast-enhanced MDCT imaging was only 70.6%. [ 21 22 ] Another Japanese study confirmed these data and showed superiority of CE-EUS in diagnosing early pancreatic cancer (≤20 mm) compared to MDCT and magnetic resonance imaging (MRI). [ 22 ] The clinical accuracy of CE-EUS for the diagnosis of PDAC versus non-PDAC lesions in pancreatic solid lesions <15 mm has been confirmed in a recent multicenter trial including 219 patients, indicating an overall 89% accuracy of CE-EUS.…”
Section: Introduction and Review Of The Literaturementioning
confidence: 91%
“…In four meta-analyses, the pooled sensitivity and specificity of CE-EUS in the diagnosis of pancreatic cancer were 91–93% and 80–88%, respectively [ 30 , 31 , 32 , 33 ]. In addition, Yamashita et al [ 34 ] reported that the sensitivity of CE-EUS for the detection of pancreatic cancer in small pancreatic masses of 11–20 mm was significantly better than that of MDCT and MRI (95% compared to 78%, and 73%, respectively), and that the sensitivity of CE-EUS in pancreatic masses of 10 mm or less was also significantly better than that of MDCT (70% and 20%, respectively).…”
Section: Eusmentioning
confidence: 99%